New records of solitary vespid wasps (Hymenoptera: Vespidae: Masarinae and Eumeninae s. l.) from the Nakhchivan Autonomous Republic of Azerbaijan - Fateryga, Alexander V.; Proshchalykin, Maxim Yu.; Maharramov, Mahir M.; Astafurova, Yulia V. (Zootaxa, 2021)
An account on 35 species in the family Vespidae (subfamilies Masarinae, Eumeninae s. str., and Raphiglossinae) is presented. Genera Jugurtia de Saussure, 1854, Quartinia André, 1884, Brachypipona Gusenleitner, 1967, and Cyrtolabulus van der Vecht, 1969, as well as 17 species and one subspecies are new to Azerbaijan. Three additional species are new to the Nakhchivan Autonomous Republic; the records of nine species confirm previous doubtful reports from the territory of the autonomy. One species is excluded from the fauna of Azerbaijan. New synonymies are proposed: Antepipona orbitalis (Herrich-Schäffer, 1839) = A. orbitalis ballioni (Morawitz, 1867), syn. nov.; A. varentzowi (Morawitz, 1895) = A. laevigata (Blüthgen, 1951), syn. nov.; Euodynerus disconotatus (Lichtenstein, 1884) = E. disconotatus sulfuripes (Morawitz, 1885), syn. nov. = E. disconotatus laniensis Giordani Soika, 1979, syn. nov.; E. semisaecularis (von Dalla Torre, 1889) = E. semisaecularis macedonicus (Blüthgen, 1951), syn. nov.; Gymnomerus laevipes (Shuckard, 1837) = G. laevipes scandinavus (de Saussure, 1856), syn. nov.; Odynerus albopictus de Saussure, 1856 = O. albopictus calcaratus (Morawitz, 1885), syn. nov. = O. albopictus kazakhstanicus Kurzenko, 1977, syn. nov. Hitherto unknown males of Brachyodynerus kusdasi Gusenleitner, 1967 and Brachypipona orientalis Gusenleitner, 2004 are described. The number of species of solitary Vespidae known from the Nakhchivan Autonomous Republic of Azerbaijan is increased to 91, with one additional subspecies which requires a revision. A preliminary list of these wasps of the whole Azerbaijan is presented; it contains 107 identified species and one additional subspecies.